Gga-miRNA-181-5p family facilitates chicken myogenesis via targeting TGFBR1 to block TGF-β signaling - Xiaoxu Shen; Yongtong Tian; Wentao He; Can He; Shunshun Han; Yao Han; Lu Xia; Bo Tan; Menggen Ma; Houyang Kang; Jie Yu; Qing Zhu; et al. (Journal of Integrative Agriculture, 2024)
MicroRNAs (miRNAs) have been demonstrated to control chicken skeletal muscle growth, however, the potential function of the miR-181-5p family in chicken myogenesis remains largely unknown. Here, our study identified the two chicken (Gallus gallus; Gga) miR-181-5p family members widely expressed in various tissues, specifically miR-181a-5p and miR-181b-5p. Besides, the breast muscles of fast-growing broilers expressed higher levels of miR-181a-5p and miR-181b-5p than those of slow-growing layers. Functionally, miR-181a-5p and miR-181b-5p both promote the expression level of myogenic factors including myogenin (MyoG), myogenic differentiation 1 (MyoD1), and myosin heavy chain (MyHC), meanwhile accelerating the myotube formation of skeletal muscle satellite cells (SMSCs). Mechanistically, miR-181a-5p and miR-181b-5p directly bind to the 3´ untranslated region (UTR) of the transforming growth factor beta receptor 1 (TGFBR1) mRNA, further reducing the expression of TGFBR1. TGFBR1 is a key Transforming growth factor beta (TGF-β) signaling transduction receptor and had a negative function in muscle cell differentiation. Furthermore, knockdown of TGFBR1 facilitated the expression of chicken myogenic factors, boosted myotube formation, and decreased the SMAD family member 2/3 (SMAD2/3) phosphorylation in chicken SMSCs. SMAD2/3 are downstream of TGF-β signaling, and miR-181a-5p and miR-181b-5p could reduce the expression of TGFBR1 to further diminish the SMAD2/3 phosphorylation. Our findings revealed that the miR-181-5p family targets TGFBR1 to break the TGF-β signaling transduction, which resulted in promoting chicken skeletal muscle development.